Strategies for recruiting and selecting teachers from the perspective of student teachers (Pedagogical Horizons, 2025)
In view of the shortage of teachers, recruitment and selection strategies are important not only for maintaining teaching but also for ensuring teaching quality. For this reason, the article examines recruitment and selection strategies from the perspective of student teachers (N = 70). Based on an open questionnaire and focus group interviews, the data, which was evaluated using content analysis, shows, among other things, that targeted recruitment programs, attractive working conditions, professional recognition, further training and career opportunities are central strategies that influence job satisfaction. On the basis of the discussed results, the article combines strategies for personnel recruitment and selection.
Keywords: teacher shortage; staff recruitment and selection; working conditions